ANALYSIS OF OCCUPATIONAL HEALTH AND SAFETY ON MALANG RAPAT VILLAGE FISHERMEN GROUP - Satriadi, Satriadi; Ridho, Muhammad Ihsan; Habibi, Umi; Usada, Julaika Fira; Martin, Diana (Balai Besar Riset Sosial Ekonomi Kelautan dan Perikanan, 2025)
This research aim to analyzed that the health and work safety of the fishermen group in Tanjung Keling Village, Malang Meeting has not been optimal, this can be seen from the indicators of occupational health and occupational safety, each of which has sub-indicators, namely in work safety, the sub-indicators are the physical work environment and the social environmentWork continuity at the fishermen group in Tanjung Keling Village, Malang Rapat. The method used in this study is qualitative method, In this study the population was 15 people then the sample used in the study was as many as 5 people. The method in this study is qualitative. Data analysis techniques use qualitative descriptive analysis techniques, then in this study to test the credibility of the data is carried out using triangulation techniques Based on the results of the study, it is known that the application of health and work safety in fishermen groups In Tanjung Keling Village, Malang Village, Meeting has not gone well, this can be due to the absence of placement of objects or items carried out as signs, boundaries, and warnings that are sufficient during fishermen's fishing, such as the depth of the coral sea and so on, many are missingFishermen admit that the rest of these danger signs, coral marks and so on they already know naturally, there used to be, but now there are none, there used to be pairs of lights, but now there are no more. Health services are very minimal, labor health facilities are still urang or even non-existent, only the initiative of the group leader to check his members regularly to the puskemas. There is no insurance for fishermen. Health services are also only limited to auxiliary health centers